PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE GROUP INVESTIGATION TERHADAP HASIL BELAJAR SISWA DI SMK NEGERI 2 GUNUNGSITOLI - Polinus Halawa; Amin otoni Harefa; Yulisman Zega (Jurnal Tunas Pendidikan, 2023)
Based on the results of initial observations in class X SMK Negeri 2 Gunungsitoli several problems were found, including: 1) Learning is still conventional (teacher centered), and 2) Student learning outcomes in mathematics are still lacking.Research objectives: (1) Describe the quality of learning mathematics through the application of the Group Investigation model. (2) Describe student learning outcomes in mathematics through the application of the Group Investigation Learning model. The research location is in class X SMK Negeri 2 Gunungsitoli. The research subjects were 26 students of class X, consisting of 12 boys and 14 girls. The research method used is Classroom Action Research (CAR), which consists of four stages: (1) Planning, (2) Action, (3) Observation, and (4) Reflection. Research instruments: (1) observation sheet, (2) learning quality questionnaire, (3) student learning achievement test, (4) interview guide sheet, and (5) photo documentation. The results of the study: (1) The quality of learning mathematics through the application of the Group Investigation learning model at X SMK Negeri 2 Gunungsitoli for the 2022/2023 academic year in Cycle I, namely 64.39%, was classified as sufficient criteria and in Cycle II, namely 98.53%, it was classified as very good criteria . (2) The average student learning outcomes in mathematics through the application of the Group Investigation learning model at X SMK Negeri 2 Gunungsitoli for the 2022/2023 academic year in Cycle I, namely 69.30, is classified as sufficient criteria and in Cycle II, namely 80.15, it is classified as criteria Good.